HIPSCS:secure IP communication system based on HIP - Min ZHOU; Ming CHEN; Chang-you XING; Pei-cheng JIANG (Tongxin xuebao)
To make the host identity protocol(HIP)into practical use,a secure communication system basd on HIP named HIPSCS was designed and implemented.HIPSCS achieved the real-name identification of communications hosts by binding the HI with user's certificates,thus made the source of packets trustworthy from network.IPsec was used to encrypt communication data,so that the goal of secure IP communication was accomplished.The HIPSCS prototype was implemented in the laboratory environment,and experimental results show that HIPSCS has good usability and can support mobile communication well.